2020
DOI: 10.3390/s20082280
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Wave Patterns Under the Region of Macro-Fiber Composite Transducer to Improve the Analytical Modelling for Directivity Calculation in Isotropic Medium

Abstract: Analytical modelling is an efficient approach to estimate the directivity of a transducer generating guided waves in the research field of ultrasonic non-destructive testing of the large and complex structures due to its short processing time as compared to the numerical modelling and experimental techniques. The wave patterns or the amplitude variations along the region of ultrasonic transducer itself depend on its behavior, excitation frequency, and the type of propagating wave mode. Depending on the wave-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…G. Lefever et al investigated the effectiveness of elastic waves for a non-destructive testing method of cementitious samples and revealed their composites of the inner structure at the microscale [17]. K. A. Tiwari et al presented a new analysis method of wave patterns from the macro-fiber composite transducer to overcome the limitation of accuracy issue of the previous analytical model [18]. They confirmed that the proposed model enhanced the analytical modeling for directivity pattern estimation.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…G. Lefever et al investigated the effectiveness of elastic waves for a non-destructive testing method of cementitious samples and revealed their composites of the inner structure at the microscale [17]. K. A. Tiwari et al presented a new analysis method of wave patterns from the macro-fiber composite transducer to overcome the limitation of accuracy issue of the previous analytical model [18]. They confirmed that the proposed model enhanced the analytical modeling for directivity pattern estimation.…”
mentioning
confidence: 90%
“…The Special Issue has been co-organized by Prof. Changho Lee, Department of Nuclear Medicine, Chonnam National University Medical School, Korea, and Prof. Changhan Yoon, Biomedical Engineering, Inje University, Korea. In this Special Issue, 17 original papers and two review papers have been published [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Most of the papers (15 papers) are in the field of biomedical engineering and four papers are related to the field of industrial applications.…”
mentioning
confidence: 99%
“…For composites with high attenuation, the ultrasound emitted by different array elements produces a large difference in the sound field energy when it is incident on the fiber layer interface, which means that the sound wave energy is correlated with its propagation direction [34]. The directivity function of the sound field from a single array element can be expressed as D(θ) [35]:…”
Section: Classical Dmas Beamforming Based On Full-matrix Datamentioning
confidence: 99%